Mycelium-bound lipase as skillful biocatalysts: Production of fatty acid concentrates from waste oils for the food industry - Matias, Alexandre B.; Reis, Willian de S.M.; Costa-Silva, Tales A.; Bento, Heitor B.S. [UNESP]; de Carvalho, Ana K.F.; Pereira, Ernandes B. (Elsevier, 2023)
This study aimed to produce Rhizopus oryzae whole-cells having high lipolytic activity. The hydrolytic activity of 558.99 U.g−1 and total lipase activity of 7440.17 U was obtained in 72 h of cultivation using 30 g.L−1 of canola oil. Optimal activity was observed at pH 7.5 and 30 °C. Kinetic parameters were determined through olive oil hydrolysis (Km = 59.96 mM, Vmax = 344.09 μmol.g−1.min−1). Thermal inactivation constant and half-life were 0.15 h−1 and 4.62 h at 50 °C. Hydrolysis of vegetable oils achieved 80% yield in 24 h. These results suggest that the biocatalyst shows the potential to produce free fatty acids of great industrial interest.
Keywords: Hydrolysis; Residual oil; Whole cell